2019
DOI: 10.1093/jxb/erz482
|View full text |Cite
|
Sign up to set email alerts
|

PAMP-INDUCED SECRETED PEPTIDE 3 (PIP3) modulates immunity in Arabidopsis thaliana

Abstract: Small post-translationally modified peptides are important signalling components of plant defence responses against phytopathogens, acting both as positive and negative modulators. PAMP-INDUCED SECRETED PEPTIDE (PIP) 1 and 2 has been shown to amplify plant immunity. Here we investigate the role of the related peptide PIP3 in the regulation of immune response in Arabidopsis. Treatment with synthetic PIP peptides led to similar transcriptome reprogramming, indicating an effect on innate immunity-related processe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 73 publications
2
19
0
Order By: Relevance
“…The co-regulation of AtWRKY33 and AtMYB46 mediates the coordination of SA and JA/ET pathways to orchestrate the defense against the phytopathogen [58]. The AtWRKY18, AtWRKY40 and AtWRKY33 act as repressors for PAMP-induced secreted peptide 3 (PIP3) to turn on the immunity via regulating SA and JA biosynthesis and signaling [59]. EF-Tu receptor (EFR) activates the SA and JA synthesis to defense against the infection, through the direct phosphorylation of a receptorlike cytoplasmic kinase (BIK1) and WRKY33, WRKY50 and WRKY57 [60].…”
Section: Discussionmentioning
confidence: 99%
“…The co-regulation of AtWRKY33 and AtMYB46 mediates the coordination of SA and JA/ET pathways to orchestrate the defense against the phytopathogen [58]. The AtWRKY18, AtWRKY40 and AtWRKY33 act as repressors for PAMP-induced secreted peptide 3 (PIP3) to turn on the immunity via regulating SA and JA biosynthesis and signaling [59]. EF-Tu receptor (EFR) activates the SA and JA synthesis to defense against the infection, through the direct phosphorylation of a receptorlike cytoplasmic kinase (BIK1) and WRKY33, WRKY50 and WRKY57 [60].…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that PIP2 and PIP3 may have different functions and/or functional mechanisms in regulating plant growth and development. As a matter of fact, it has been shown that PIP2 and PIP3 regulate plant biotic response in different ways, PIP2 regulates antipathogen activity by regulating the expression of some PTI-related genes, WRKY genes, flg22-induced receptor-like kinase 1 (FRK1) and the SAR marker gene PR-1 (Chen et al, 2019b), whereas PIP3 regulates immunity by regulating the biosynthesis and signaling of SA and JA in Arabidopsis (Najafi et al, 2020). On the other hand, both PIP2 and PIP3 contain two conserved SGPS motifs (Vie et al, 2015), and may able to produce two mature peptides, which may have different functions.…”
Section: Discussionmentioning
confidence: 99%
“…Both PIP and PIPL propeptides have an N-terminal signal peptide and a C-terminal SGPS motif, which is part of the biologically active peptides, with an exception of PIP2 and PIP3 prepropeptides, which have two SGPS motifs (Hou et al, 2014;Vie et al, 2015). The PIP peptides including PIP1, PIP2 and PIP3 have been shown to modulate immunity (Hou et al, 2014;Najafi et al, 2020), and the expression of several PIPs and PIPLs family genes is induced by biotic and/or abiotic stresses (Hou et al, 2014;Vie et al, 2015). On the other hand, it has been reported that the PIPL3/TARGET OF LBD SIXTEEN 2(TOLS2) is able to regulate lateral root formation (Toyokura, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…There were no major differences between the different time points in the Arabidopsis model (Attard et al, 2014), between P. palmivora and P. megakarya infections in the Theobroma model (Ali et al, 2017), or between resistant and susceptible Soybean lineages (Lin et al, 2014) (Figure 2a). The two Arabidopsis members of this cluster have been described previously as the source of the PAMP-induced peptides PIP2 and PIP3; the corresponding gene names are PREPIP2 and PREPIP3 (Vie et al, 2015;Najafi et al, 2020;Hussain et al, 2021). A third published PIP-encoding gene, AT4G28460/PREPIP1 (Hou et al, 2019;Shen et al, 2020), is more divergent and therefore not a member of the upregulated PREPIP2/3 sequence cluster.…”
Section: Strong Induction Of Secreted Peptide Precursorsmentioning
confidence: 99%